Develop and Implementation of Autonomous Vision Based Mobile Robot Following Human - Mohd Shah, Hairol Nizam; Ab Rashid, Mohd Zamzuri (2013)
This project related to develop and implementation of autonomous vision based mobile robot following human. Human tracking algorithm will be developed to allow a mobile robot to follow a human.